(untitled) (Research, Society and Development, 2024)
Sports dentistry aims to promote health, improve performance and prevent injuries in athletes. It is necessary for the dental surgeon to participate in the routine of athletes from the youth categories, including athletes with intellectual, physical and visual disabilities, this group presents several changes in the oral cavity because of their limitations. The participation of the Brazilian team in the Paralympic Games since 1972, became essential to evaluate oral health problems in these athletes and rehabilitate them, providing better results in competitions. Methodology: 20 articles were selected between 2005 and 2021, indexed in the Pubmed, scholar and lilacs database, using the descriptors ‘’Dentistry”, “Oral health”, “Sports Medicine”, “Disabled Persons” and “Sports for Persons with Disabilities”. Oral injuries in Brazilian para-athletes, bruxism, mouth breathing and recurrent oral herpes lesions are the most frequent problems and can negatively affect the performance of these athletes. There is a high need dental care practices for patients with special needs at the University Dentistry. There was a significant need for attention and dental treatment for athletes with intellectual disabilities, and it is important to invest in strategies that promote self-care in order to improve daily hygiene. It is necessary for dental surgeons to work in Paralympic sports, meeting the individual needs of athletes with access to quality oral health and adequate monitoring, in order to improve performance and avoid complications that affect the quality of sports practice. The objective for this article is review the literature on the importance of dental surgeons in Paralympic sports.